2017
DOI: 10.1002/jcp.26242
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of dying beta cell originated messenger molecules in differentiation of pancreatic mesenchymal stem cells under glucotoxic and glucolipotoxic conditions

Abstract: Beta cell mass regulation represents a critical issue for understanding and treatment of diabetes. The most important process in the development of diabetes is beta cell death, generally induced by glucotoxicity or glucolipotoxicity, and the regeneration mechanism of new beta cells that will replace dead beta cells is still not fully understood. The aim of this study was to investigate the generation mechanism of new beta cells by considering the compensation phase of type 2 diabetes mellitus. In this study, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…CK18 M65ED can act as a cell death marker in cardiometabolic disorders because of its ability to detect both native and intact CK18 [18]. Previous studies have demonstrated that apoptosis can cause a decrease in the number of circulating mucosalassociated invariant T cells in cardiometabolic diseases [7]. Moreover, myocardial cells undergo death in obesityassociated cardiomyopathy in high-fat diet-fed mice [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CK18 M65ED can act as a cell death marker in cardiometabolic disorders because of its ability to detect both native and intact CK18 [18]. Previous studies have demonstrated that apoptosis can cause a decrease in the number of circulating mucosalassociated invariant T cells in cardiometabolic diseases [7]. Moreover, myocardial cells undergo death in obesityassociated cardiomyopathy in high-fat diet-fed mice [8].…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Diabetes Research proportion of regulatory T cells within the gut [43]. Touch et al have suggested that apoptosis of mucosal-associated invariant T cells in patients with cardiometabolic disorders occurs due to gut microbiome dysbiosis and enhanced proapoptotic signaling, which is caused by long-term and low-grade systemic inflammation [7]. The pathway in which CK18 is involved in cell death at a molecular level is, however, not very clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differentiation capacity of ARIP cells to pancreatic β‐cells and adipocytes was checked by application of differentiation protocols published before (Gezginci‐Oktayoglu et al, 2018). Briefly, for β‐cell differentiation ARIP cells were cultured with 10 mM nicotinamide, 1 mM mercaptoethanol in Dulbecco's modified Eagle's medium (DMEM) with 5.5 mM glucose for 24 h and then the same content was applied in DMEM with 25 mM glucose for 24 h under standard culture conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Ainda, mudanças metabólicas nas células β-pancreáticas também podem ocorrer como resposta a diversos agentes estressores. Em apoptose de células β primárias, além de insulina, onze novas Cholesterol proteínas foram secretadas, entre elas a alfa-1-glicoproteína ácida (AGP), enzima aldolase frutose 1,6 bifosfato, STAM-binding protein, Interleukin-1-receptor-like 1 (IL1RL1) e brain-specific angiogenesis inhibitor 1-associated protein 2-like protein 1 (BAIAP2L1) (Gezginci-Oktayoglu et al, 2018). Ainda, em ilhotas pancreáticas apresentando disfunção na secreção de insulina e comprometimento da atividade oxidoredutase, identificou-se 262 proteínas secretadas, incluindo a AGP e a enzima aldolase frutose 1,6 bifosfato, bem como proteína ligadora de ácidos graxos, anexina A5 e glutationa peroxidase 1 (Kuo et al, 2016).…”
Section: •-unclassified